Evaluation of Socially and Culturally Coordinated Development in Cities of Yangtze River Economic Belt and Its Spatial Correlation - Zhenzhen Yi; Xianzhong Cao; Liuting Qin (Land, 2025)
In the process of Chinese-style modernisation, the socially and culturally coordinated development of cities in the Yangtze River Economic Belt is important for promoting regional coordinated development, enhancing the balance of public services, and strengthening cultural soft power. This study used quantitative methods, including the construction of an indicator system, spatial correlation analysis, and Zipf’s rank-size rule, on data from 2011 to 2021 to analyse the capacity for coordinated social and cultural development and assessed the spatial distribution characteristics of the Yangtze River Economic Belt. The study found that the overall level of social and cultural coordination among the cities in the Yangtze River Economic Belt steadily improved; however, significant regional disparities still exist, particularly in areas such as social security and cultural integration. Spatially, a “high in the east, low in the west” pattern is observed, with the Yangtze River Delta city cluster leading development, the midstream cluster playing a supportive role, and the Chengdu–Chongqing city cluster showing significant internal disparities. Core cities such as Shanghai, Hangzhou, Wuhan, and Chengdu demonstrated driving effects in areas such as culture, education, and healthcare; however, some peripheral cities remain underdeveloped. This study suggests the need to enhance the development of the Yangtze River’s culture, promote the development of cultural industry clusters, foster the integration of various business models, leverage scientific and educational resources, optimise the cultural consumption market, and achieve the coordinated development of the social and cultural sectors, thereby enabling the Yangtze River Economic Belt to play a greater role in Chinese-style modernisation.